Conform or Nonconform? Observational Learning and Social Preference - Sasaki, Shunichiro (Journal of Behavioral Economics and Finance, 2010)
This study investigates the influence of the observational learning about other peoples’behaviors on the subject’s social preference. To do this, we conducted the web-based experiment in the U.S., Japan, and China and 4200 subjects participated in the experiment. In the experiment subjects played the modified dictator game twice under the both circumstances where they cannot observe other people’s behaviors and where they can observe them. If a subject changes the behavior after the observational learning, we regard the subject as being influenced by it. We categorize such behavioral change into altruistic conformity, selfish conformity, altruistic nonconformity, and selfish nonconformity. Then, we measured the influence of observational learning on the subject’s social preference. We observed that (1) after the observational learning the Japanese subjects become more altruistic and the Chinese subjects become more selfish whereas the U.S. subjects do not change their behaviors, (2) the proportion of behavioral change toward conformity is higher than that toward nonconformity, (3) younger subjects are more likely to change their behavior altruistically than older subjects (4) female subjects are more likely to exhibit altruistic conformity than male subjects (5) subjects tend to exhibit altruistic conformity and selfish nonconformity as the number of other people who behave altruistically increases whereas they tend to exhibit selfish conformity and altruistic nonconformity as the number of other people who behave selfishly increases. These findings imply that the observational learning about other peoples’ behaviors may change subject’s social preference and it has various influences on subject’s altruism and conformity.